Spatio-temporal variation and seasonal dynamics of stranded beach anthropogenic debris on Indonesian beach from the results of nationwide monitoring. (September 2022) - Cordova, Muhammad Reza; Iskandar, Mochamad Riza; Muhtadi, Ahmad; Nurhasanah; Saville, Ramadhona; Riani, Etty
Abstract: The first stranded macrodebris study on a national scale in Indonesia was conducted on 18 beaches from February 2018 to December 2019. The average weight and abundance of beach debris were higher between October and February (rainy season). The highest stranded macrodebris was located in Ambon, Manado, Takalar, and Padang. Plastic (46.38 %) was the most prevalent type of debris across all macrodebris categories, with single-use plastics such as plastic sachets, plastic bags, and plastic bottles being the dominant macroplastic debris (64.64 %). Based on CCI, HII, and BGI, 18 beaches are "moderately clean, " with few hazardous items observed, and "Good." This anthropogenic macrodebris is thought to be more localized (55 %) than transboundary macrodebris. Litter control and environmental quality of this Indonesian coastal region should be improved through a proactive and flexible approach. Finally, extensive stranded beach debris monitoring is recommended to better understand the distribution of macrodebris in the region. Highlights: First comprehensive spatial and temporal of Indonesian stranded debris were done. Debris was found on Indonesian beaches throughout the sampling period. The number of beach debris varies significantly during the rainy season. Single-use plastic that relatively direct recycling is more prevalent outside Java Island. Sources of stranded beach debris are predominantly local rather than transboundary.